Sexual Dimorphism of Atherosclerosis by Gut Microbiome in a Hyperlipidemic Diversity Outbred F1 Mouse Population. (29th May 2020) - Kim, Myungsuk; Huda, M Nazmul; Que, Excel; Gertz, Erik; Bennett, Brian
Abstract: Objectives: Atherosclerosis is a complex multifactorial disease that develops through the interaction of various genetic and environmental factors. The environmental factors affecting atherosclerosis susceptibility include gender differences and the gut microbiota. However, the association between sex, microbiota, and atherosclerosis remains unclear. We hypothesized that the association between gut microbial profiles and atherosclerosis demonstrates sexual dimorphism. In order to test this hypothesis, we examined atherosclerosis and microbiota in a population of hyperlipidemic outbred mice. Methods: We collected offspring (262 female and 269 male mice) from a cross between hyperlipidemic male C57BL/6J mice, transgenic for both human apolipoprotein E-Leiden and cholesterol ester transfer protein genes, and ∼200 female Diversity Outbred (DO) mice, a population derived from 8 inbred strains. We fed the offspring a high fat/cholesterol diet for 12 weeks. We then examined over 20 cardio-metabolic traits and their fecal microbiota compositions using 16S rRNA sequencing. Results: Female mice were significantly more susceptible to atherosclerosis with higher lesion area ( P  < 0.0001) and plasma cholesterol ( P  < 0.0001) than males. For gut microbiota analysis, females had higher microbial α-diversity (Shannon diversity, P  < 0.0001) than males and their β-diversity (Unweighted UniFrac, R 2  = 0.01, PERMANOVA < 0.001) showed that the overall community is significantly different. We also examined the association between sexually-dimorphic gut phylotypes and cardiometabolic phenotypes and identified a negative correlation between atherosclerosis and the abundance of the genus Bifidobacterium, while abundances of genus Lactococcus were positively associated with atherosclerosis. Upcoming studies will be designed to identify host genes affecting microbiota abundance and functional characterization of specific microbiota-atherosclerosis traits. Conclusions: To the best of our knowledge, this study suggests the first example of complex interactions between sexually dimorphic traits and gut microbiota associated with atherosclerosis using DO-F1 mice. Funding Sources: This work was supported by the National Heart, Lung, and Blood Institute.